2023
DOI: 10.1186/s12889-023-15692-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the participation of men in reproductive health care: a systematic review and meta-synthesis

Abstract: Background Despite emphasizing the importance and benefits of men's active engagement in reproductive health programs, their engagement in reproductive health care is low. Researchers have identified different barriers to men's avoidance of participation in various aspects of reproductive health in different parts of the world. This study provided an in-depth review of the hindrances to men’s non-participation in reproductive health. Methods This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The authors emphasize the need for culturally sensitive approaches that recognize and address power dynamics, social norms, and gender inequalities (Greene et al, 2006). However, there are some barriers to men's participation in reproductive health care, such as social norms, dominant culture, social stigma, lack of services in low-income countries, and financial restrictions, among others (Roudsari et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…The authors emphasize the need for culturally sensitive approaches that recognize and address power dynamics, social norms, and gender inequalities (Greene et al, 2006). However, there are some barriers to men's participation in reproductive health care, such as social norms, dominant culture, social stigma, lack of services in low-income countries, and financial restrictions, among others (Roudsari et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…The few studies in African countries focusing on men’s healthcare needs have revealed significant barriers and challenges hindering their access and utilization of healthcare services [ 6 , 22 ]. Financial constraints emerge as a significant hurdle, deterring some men from seeking healthcare when needed [ 6 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies in African countries focusing on men’s healthcare needs have revealed significant barriers and challenges hindering their access and utilization of healthcare services [ 6 , 22 ]. Financial constraints emerge as a significant hurdle, deterring some men from seeking healthcare when needed [ 6 , 22 , 24 ]. Furthermore, negative perceptions and attitudes towards healthcare services, often fuelled by fears of stigmatization and mistreatment, act as barriers to engagement [ 22 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that the supply is not the issue ( Shelton & Jacobstein, 2016 ), concerns have been raised about biases and knowledge among non-vasectomy providers. A recent systematic review of barriers to male participation in general reproductive health care highlighted that barriers to inclusive and integrated quality reproductive health services are the primary limitation to male engagement in reproductive health, and pointed to health care workers as a major contributor to the lack of access to reproductive health services ( Roudsari et al , 2023 ). Another recent study similarly highlighted that many health professionals involved in contraception have unsatisfactory knowledge of male contraceptive methods and are not reliably offering male options during couple contraceptive counseling sessions ( Tcherdukian et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%